2024
DOI: 10.3389/fmicb.2023.1272892
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance of Salmonella in organic and non-organic chickens on the Eastern Shore of Maryland, USA

Anuradha Jeewantha Punchihewage-Don,
Jurgen Schwarz,
Abdirahman Diria
et al.

Abstract: IntroductionSalmonella infections have been intensely increasing and becoming a universal public health crisis. This study investigated the prevalence of Salmonella in organic and non-organic chickens and the antimicrobial resistance profiles and virulence genes (invA, pagC, and spvC) in recovered Salmonella isolates.MethodsWhole chicken carcasses [organic (n = 240) and non-organic (n = 240)] were obtained monthly for 1 year (n = 480) from a retail store on the Eastern Shore of Maryland. Salmonella isolation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, a prior study on non-ripened cheese by Oladapo et al [20] from Nigeria identified S. Typhimurium isolates as stn and hilA positive, but spvC-negative, which is in contrast with our current research. The limited incidence of spvC-positive strains in our study may be attributed to the unstable plasmid-located genes, which are lost through repeated sub-culturing steps [29,30].…”
Section: Discussionmentioning
confidence: 79%
“…However, a prior study on non-ripened cheese by Oladapo et al [20] from Nigeria identified S. Typhimurium isolates as stn and hilA positive, but spvC-negative, which is in contrast with our current research. The limited incidence of spvC-positive strains in our study may be attributed to the unstable plasmid-located genes, which are lost through repeated sub-culturing steps [29,30].…”
Section: Discussionmentioning
confidence: 79%